Analisis Pemanfaatan Digital Marketing Sebagai Media Membangun Jaringan Bisnis pada UMKM Milan Food - Marselina, Resya Dwi; Fadillah, Ajeng Ismil; Hendriawan, Rian; Azzahra, Intan Yulia (Melati Institute, 2024)
This study aims to determine the benefits of digital marketing as a medium for building business networks in Milan Food MSMEs. This research uses qualitative methods, the technical data analysis used in this research is by interviewing the business owner or owner of Milan Food. And get results that show that the role of digital marketing affects the development of the Milan Food business network. The business network is the key to success and has a very influential factor in the marketing of Milan Food. With digital technology, business people can look for opportunities with business strategies to make sales, the business strategy carried out is through marketing.